5,5′-Bis[(1H-imidazol-1-yl)methyl]-2,2′-bipyridine methanol disolvate - Moon, Suk-Hee (International Union of Crystallography, 2011)
The title compound, C(18)H(16)N(6)·2CH(3)OH, was prepared by the reaction of 5,5′-bis(bromomethyl)-2,2′-bipyridine with imidazole. The main molecule lies on an inversion center located at the mid-point of the C—C bond joining the two pyridine rings. The asymmetric unit therefore contains one half-molecule and one methanol solvent molecule. The dihedral angle between the pyridine and imidazole rings is 72.32 (5)°. In the crystal, weak intermolecular O—H⋯N, C—H⋯N and C—H⋯O hydrogen bonds contribute to the stabilization of the packing.